Extreme nouns and maximizers - Masià, Melania S. (Proceedings of Sinn und Bedeutung, 2019)
Maximizers (completamente ‘completely’, totalmente ‘totally’) are degree modifiers restricted to maximum standard adjectives. Spanish adjectives of completeness [ACs] (completo ‘complete’, total ‘total’) display a behavior similar to that of their adverbial counterparts when they combine with nouns like idiot. This paper argues that ACs are maximality modifiers of idiot-like nouns, which are defended to be gradable and denote extreme degrees of properties. Establishing a parallelism between adverbs and adjectives of completeness allows us to explore scalarity across categories and the relevance of scale structure in the nominal domain.